Pathogenicity of Nc-Bahia and Nc-1 strains of Neospora caninum in experimentally infected cows and buffaloes in early pregnancy - Chryssafidis, Andreas Lazaros; Canton, German Jose; Chianini, Francesca; Innes, Elisabeth A.; Madureira, Ed Hoffmann; Gennari, Solange Maria (Springer, 2019)
Neospora caninum is a protozoan parasite known as an important cause of bovine abortion worldwide. Little is currently known about how different strains of N. caninum vary in their pathogenicity. In this study, we compared a Brazilian strain, Nc-Bahia, with the first isolate of this coccidian, Nc-1. Eight cows and seven buffaloes were submitted to fixed-time artificial insemination protocols for a better control of pregnancy. Group 1 was inoculated with Nc-Bahia (n = 8; five cows and three buffaloes), and Group 2 was inoculated with Nc-1 (n = 5; two cows and three buffaloes). One nonpregnant female of each species was left uninfected as sentinel controls for potential environmental infection. All inoculated animals received 5 × 108 tachyzoites of N. caninum, by intravenous route, on the 70th day of gestation. Uninfected animals remained seronegative throughout the experiment, indicating no exogenous infection, whereas all inoculated animals became seropositive to N. caninum. In Group 1, abortion was found in only one cow on 42 days postinfection (dpi; frequency of abortion = 12.5 %), whilst all animals from Group 2 aborted on 35 dpi (frequency of abortion = 100 %). Parasite DNA was detected by seminested PCR in maternal, foetal and placental tissues, confirming vertical transmission in Groups 1 and 2, although histological lesions had different frequencies and degrees of severity between the groups. There was evidence of lower pathogenicity of Nc-Bahia compared to Nc-1 when used in experimental infection, as it caused fewer abortions, as well as less frequent and milder histological lesions. This was the first time Nc-Bahia has been used for experimental infection.